Jane Austen : two centuries of criticism - Mazzeno, Laurence W. (Rochester, N.Y. : Camden House, 2011)
Among the most important English novelists, Jane Austen is unusual because esteemed not only by academics but also by the reading public: her novels continue to sell well, and films adapted from her works enjoy box-office success. The trajectory of Austen criticism is intriguing, especially when one compares it to that of other nineteenth-century English writers. At least partly because she was a woman in the early nineteenth century, she was long neglected by critics, hardly considered a major figure in English literature until well into the twentieth century, a hundred years after her death. But consequently she escaped the reaction against Victorianism that did so much to hurt the reputation of Dickens, Tennyson, Arnold, and others. How she rose to prominence among academic critics--and has retained her position through the constant shifting of academic and critical trends--is a story worth telling, as it suggests not only something about Austen's artistry but also how changes in critical perspective can radically alter a writer's reputation.
Introduction -- Becoming England's Jane, 1811-1917 -- Modernist, humanist, and new critical approaches, 1918-1948 -- The zenith of formalist and humanist criticism, 1949-1974 -- The Austen bicentenary, 1975 (and beyond) -- The feminist revolution in Austen studies, 1976-1990 -- Austen among the theorists, 1976-1990 -- Traditional criticism, 1976-1990 -- Theory-based criticism of Austen, 1991-2008 -- Traditional approaches to Austen, 1991-2008 -- Speculations on the future -- Works by Jane Austen -- Chronological list of works cited.
Includes bibliographical references (pages 247-288) and index.
Print version record.
JSTOR
Keywords: Austen, Jane, -- 1775-1817 -- Criticism and interpretation -- History; Austen, Jane, -- 1775-1817; Austen, Jane -- 1775-1817; Austen, Jane; Austen, Jane, -- 1775-1817 -- Criticism and interpretation -- History; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh; LITERARY CRITICISM -- American -- General; Rezeption; Receptie; Rezeption; Criticism, interpretation, etc; History